Thrust characteristics research on continuous rotating detonation engine - Wang, Qingwu; Zhang, Shihui (Case studies in thermal engineering, 2023)
Detonation combustion can produce pressure enhancement effect, increasing engine thrust. In this paper, a 2D Euler control equation with chemical reaction is used to solve the periodic flow of the detonation wave in a rectangular plane. The combustion of the air-breathing continuous rotating detonation engine is simulated. The RDE thrust is obtained through the outlet parameters of the engine. The fuel used is hydrogen, with the equivalent ratio to air. The calculation reflects the working condition of the engine running at low speed. The operating conditions of the engine at low speed are calculated, with a low intake pressure and temperature of 300K and 0.2/0.35 MPa respectively. It is found that the thermal efficiency of detonation wave is higher than that of the deflagration wave under low inlet pressure and temperature, and the thrust of RDE is significantly higher than that of the deflagration engine. The pressure enhancement effect of RDE is not as strong as that of detonation wave, so the pressure ratio of detonation wave can not be used to calculate the engine efficiency.